Agrotóxicos e sustentabilidade: percepção dos sujeitos sociais no meio rural - Bohner, Tanny Oliveira Lima (2015)
Current agricultural production methods are highly dependent of inputs and pesticides, often considered necessary for the viability of vegetable crop production. However, the intensive and excessive use of such inputs leads to harmful effects on the environment, as well as public health hazards. In this regard, small farms are particularly vulnerable to a wide range of health effects related to pesticide exposure. Thus, considering both social and environmental impacts of using such hazardous substances in crop production, this master thesis aims to understand the perception of farmers and professionals who disseminate information concerning pesticide use in agricultural activities of Chapecó, SC. In order to obtain primary research data, three Rural Extension Agents from Agricultural Research and Rural Extension Company of Santa Catarina (EPAGRI) were first interviewed. Then, semi-structured questionnaires were applied to 18 local farmers who growed horticultural crops, with regard to risk perception, knowledge of biosecurity guidelines and other forms of cultivation, as well as attitudes and practices related to pesticide use. Subsequently, 6 organic farmers were interviewed through questionnaires containing open-ended questions adressing the same aspects, as well as sustainable production systems. The results showed that few conventional farmers have the required expertise to handle risky and dangerous products. In this sense, few pesticide users often read the agronomic prescription and understand the information and instructions before using these products. Most of farmers know proper storage practices, altough they usually do not sign it properly. Users reported to use Personal Protective Equipment (PPE), however they do it partially. On the other hand, organic farmers do recognize the potential harmful effects of pesticide exposure. Conversely, conventional farmers, even when aware of the risks of the handling this substances, often incorrectly believe these products are safe if properly used. Furthermore, Rural Extension Agents, who are experts on the subject, always recognize the risks of pesticides use. Despite this recognition, the low incentive of public agencies limits their actions. Therefore, there is a need for educational activities in order to increase information and awareness of farmers regarding the risks and consequences of pesticides handling, since the misuse leads to a wide range of harmful consequences, which damages not only the environment and nature as a whole, but especially the public health. Therefore, farmers must be informed about sustainable agricultural methods and management techniques, based on scientific principles and practices of Agroecology.